Innovative Community Tourism in Uganda: International Tourists, National Networks, and Local Livelihoods - MacKay, Kelly; Campbell, J. (Téoros, 2012)
This paper illustrates an innovative approach to enhance rural livelihoods through community tourism in Uganda. Following pro-poor tourism principles of local participation and linking with existing systems, Gorilla Friends Tented Camp opened in Ruhija village, where mountain gorillas were recently habituated for gorilla tracking tours. In a village that had no previous tourist accommodations and few opportunities for villagers to earn income, a percentage of profits from Gorilla Friends Tented Camp are returned to support other livelihood enhancement initiatives in the village. While much of our previous research has focused on identifying and developing local capacity to participate meaningfully in Uganda’s tourism industry, attention must also be paid to tourists’ experiences at the site to ensure continued viability. Findings based on interviews with tourists to Ruhija illustrate the need for national partnership networks to support local community tourism. Additionally, understanding how tourists came to and experienced the community will assist the local people with sustainability of their operations and activities, and inform continued innovation in community tourism development in Ruhija.